An experimental investigation on the workability of eco-friendly self-compacting concrete using bamboo leaf ash as a partial cement replacement - Tushar, Fazlul Hoque; Manjur, Kazi Abu; Hasan, Kamrul; Khan, Asif; Hossain, Md. Amzad; Alakhali, Ahmed K.; Fadzil, Mat Yahaya (IOP Publishing, 2025)
This study investigates the use of bamboo leaf ash (BLA) as a partial replacement for cement in the development of self-compacting concrete (SCC) for sustainable development and construction practice. This study was conducted in Bangladesh, a country with vast bamboo resources. The study focuses on the assessment of the chemical properties of BLA, workability, environmental impact, and cost-effectiveness. The chemical analysis showed that BLA has a high silicon content of 84.81%, making it an excellent pozzolanic material. Concrete mixtures with BLA replacing cement at 0%, 2.5%, 5%, and 10% by weight were tested. The results showed that all mixes maintained acceptable workability within the EFNARC and ASTM recommended limits. Also, the environmental impact assessment demonstrated a 9.30% decrease in carbon dioxide (CO2) emissions and a 4.95% cost reduction in concrete production with a 10% BLA replacement, highlighting significant ecological and economic benefits. These results depict the viability of BLA as a sustainable building material and suggest its potential practical applications in the construction industry.